Separator for rechargeable lithium battery and rechargeable lithium battery comprising the same

CN123018355APending Publication Date: 2026-10-30SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610329087.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-28
Filing Date
2026-03-18
Publication Date
2026-10-30

Smart Images

  • Figure CN123018355A_ABST
    Figure CN123018355A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a separator for a rechargeable lithium battery and a rechargeable lithium battery including the same. The separator for a rechargeable lithium battery includes a porous substrate and a coating layer on at least one surface of the porous substrate. The coating layer includes a binder and an additive including one or more of a compound, an oligomer of the compound, and a polymer of the compound.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority and benefit to Korean Patent Application No. 10-2025-0055071, filed on April 28, 2025, with the Korean Intellectual Property Office, the entire disclosure of which is incorporated herein by reference. Technical Field

[0002] This disclosure relates to a separator for a rechargeable lithium battery and a rechargeable lithium battery including the separator. Background Technology

[0003] With the increasing prevalence of battery-powered electronic devices (such as mobile phones, laptops, and electric vehicles), the demand for rechargeable batteries with high energy density and high capacity is growing. Therefore, research and development to improve the performance of rechargeable lithium batteries is actively underway.

[0004] Rechargeable lithium batteries typically include a positive electrode and a negative electrode containing active materials capable of inserting and deintercalating lithium ions, and generate electrical energy through oxidation and reduction reactions when lithium ions insert into the positive electrode and deintercalate from the negative electrode, and when lithium ions insert into the negative electrode and deintercalate from the positive electrode.

[0005] Rechargeable lithium batteries may include a separator between the positive and negative electrodes. Summary of the Invention

[0006] One example embodiment includes a separator for rechargeable lithium batteries that provides high adhesive strength and low membrane resistance.

[0007] According to another example embodiment, the separator for a rechargeable lithium battery reduces or suppresses ignition when the battery is exposed to heat.

[0008] Another example embodiment includes a rechargeable lithium battery comprising a positive electrode, a negative electrode, and a separator for rechargeable battery located between the positive and negative electrodes.

[0009] According to one example embodiment, a separator for a rechargeable lithium battery is provided.

[0010] The separator for a rechargeable lithium battery includes a porous substrate and a coating on at least one surface of the porous substrate. The coating includes a binder and additives, and the additives include one or more of compounds of Formula 1 below, compounds of Formula 2 below, oligomers thereof, and polymers thereof: Chemical Formula 1: .

[0011] In chemical formula 1, R1 to R6 are all as described below.

[0012] Chemical formula 2: .

[0013] In chemical formula 2, R7 to R 14 All are as described below.

[0014] Another example embodiment includes a rechargeable lithium battery.

[0015] The rechargeable lithium battery includes a positive electrode, a negative electrode, and a separator for the rechargeable lithium battery located between the positive and negative electrodes. Attached Figure Description

[0016] The above and other objects, features, and advantages of this disclosure will become more apparent to those skilled in the art from the detailed description of exemplary embodiments with reference to the accompanying drawings, in which: Figure 1 This is a cross-sectional view showing a separator for a rechargeable lithium battery according to an example embodiment; Figure 2 This is a cross-sectional view showing a separator for a rechargeable lithium battery according to another example embodiment; Figure 3 This is a cross-sectional view showing a separator for a rechargeable lithium battery according to yet another exemplary embodiment; Figures 4 to 7 This is a schematic diagram illustrating a rechargeable lithium battery according to an example embodiment. Detailed Implementation

[0017] In the following, exemplary embodiments of the present disclosure may be described in detail. However, the embodiments are provided as examples, and the present disclosure is not limited thereto, and is limited only by the scope of the appended claims.

[0018] Unless otherwise stated herein, when a component such as a layer, film, region, plate, etc., is described as being “on” another component, it includes not only the case where the component is “directly on” the other component, but also the case where there is another component between them.

[0019] Unless otherwise stated in this specification, anything indicated in the singular may also include the plural. Furthermore, unless otherwise stated, “A or B” may mean “including A, including B, or including both A and B”.

[0020] As used herein, the term "combination of them" may refer to mixtures, laminates, complexes, copolymers, alloys, blends, and reaction products of the components.

[0021] Here, the term "particle size D50" refers to the average particle size, which represents the diameter of particles that constitute 50% of the cumulative volume in the particle size distribution. Particle size distribution can be measured using methods known to those skilled in the art. For example, particle size distribution can be measured using a particle size analyzer, transmission electron microscopy, or scanning electron microscopy. In another method, the D50 value can be obtained by measuring the particle size using a measuring device that utilizes dynamic light scattering, performing data analysis to calculate the number of particles for each particle size range, and then calculating the particle size from that. Alternatively, D50 can be measured using laser diffraction. For example, when measured by laser diffraction, after dispersing the particles to be measured in a dispersion medium, the particles can be introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasound at approximately 28 kHz at an output of 60 W, and D50 can be calculated based on 50% of the particle size distribution in the measuring device.

[0022] In this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0023] Unless otherwise defined herein, “substitution” means that hydrogen in a compound is substituted by a substituent, which is such as or includes C1 to C30 alkyl, C2 to C30 alkenyl, C2 to C30 alkynyl, C6 to C30 aryl, C7 to C30 alkylaryl, C1 to C30 alkoxy, C1 to C30 heteroalkyl, C3 to C30 heteroalkylaryl, C3 to C30 cycloalkyl, C3 to C15 cycloalkenyl, C6 to C30 cycloalkynyl, C2 to C30 heterocycloalkyl, halogen (F, Cl, Br or I), hydroxyl (-OH), nitro (-NO2), cyano (-CN), amino (-NRR') (wherein R and R' are each independently hydrogen or C1 to C6 alkyl), sulfobetaine (-RR'N) + (CH2) n SO3 - n is a natural number in the range of 1 to 10 (where R and R' are each independently a C1 to C20 alkyl group), carboxybenzene group (-RR'N) + (CH2) n COO -The following groups are used: n is a natural number in the range of 1 to 10 (where R and R' are each independently C1 to C20 alkyl groups), azide (-N3), amidine (-C(=NH)NH2), hydrazine (-NHNH2), hydrazone (=N(NH2)), carbamoyl (-C(=O)NH2), thiol (-SH), acyl (-C(=O)R, where R is hydrogen, C1 to C6 alkyl, C1 to C6 alkoxy or C6 to C12 aryl), carboxyl (-COOH) or a salt thereof (-C(=O)OM, where M is an organic or inorganic cation), sulfonic acid (-SO3H) or a salt thereof (-SO3M, where M is an organic or inorganic cation), phosphate (-PO3H2) or a salt thereof (-PO3MH or -PO3M2, where M is an organic or inorganic cation), and at least one combination thereof.

[0024] In the following text, C1 to C3 alkyl means methyl, ethyl, or propyl. C1 to C10 alkylene can be, for example, C1 to C6 alkylene, C1 to C5 alkylene, or C1 to C3 alkylene, such as methylene, ethylene, or propylene. C3 to C20 cycloalkylene can be, for example, C3 to C10 cycloalkylene or C5 to C10 cycloalkylene, such as cyclohexylene. C6 to C20 arylene can be, for example, C6 to C10 arylene, such as phenylene. C3 to C20 heterocyclic can be, for example, C3 to C10 heterocyclic, such as pyridyl.

[0025] In the following text, “heterogeneous” means including one or more heteroatoms, such as being or including at least one of N, O, S, Si and P.

[0026] In chemical formulas, Symbols indicate portions that are connected to the same or different atoms, groups, or structural units. Unless otherwise specified in the chemical formulas described herein, it can be assumed that hydrogen bonds are present in the structure of the chemical formulas.

[0027] In the following text, "alkali metals" refers to elements belonging to Group 1 of the periodic table, such as lithium, sodium, potassium, rubidium, cesium, or francium, which can exist in either a cation or a neutral state.

[0028] When describing numerical ranges in this specification, “X to Y” means “X or greater and Y or less (greater than or equal to X and less than or equal to Y)”.

[0029] When the terms “about” or “substantially” are used in conjunction with numerical values ​​in this specification, it means that the relevant numerical value includes a tolerance of ±10% around the stated value. When a range is specified, the range includes all values ​​within that range, such as increments of 0.1%.

[0030] According to one example embodiment, the separator for a rechargeable lithium-ion battery can provide high adhesive strength. For example, the separator can provide high wet adhesive strength for both the positive and negative electrodes. Therefore, the separator can provide low thermal shrinkage, long room temperature life, and long high temperature life. Specifically, even when the battery is left to stand at high temperatures after a room temperature life evaluation, the separator can improve battery reliability by providing low thermal shrinkage.

[0031] According to one example embodiment, the separator for a rechargeable lithium battery can provide long room temperature lifetime and long high temperature lifetime by providing low membrane resistance (e.g., electrochemical impedance spectroscopy (EIS) membrane resistance).

[0032] According to one example embodiment, a separator for a rechargeable lithium battery can improve the safety and reliability of the battery by reducing or suppressing the ignition of the battery with the separator when exposed to heat.

[0033] According to one example embodiment, the diaphragm includes a porous substrate and a coating on at least one surface of the porous substrate. The coating includes an adhesive and additives, the additives including one or more of compounds of Formula 1 below, compounds of Formula 2 below, oligomers thereof, and polymers thereof.

[0034] The compounds of Formula 1 below, the compounds of Formula 2 below, the oligomers and the polymers can simultaneously or concurrently provide high adhesive strength and low film resistance.

[0035] Compounds of Formula 1, compounds of Formula 2, oligomers, and polymers can be included in a coating together with the binders and / or fillers described below to increase the adhesive strength of the coating, thereby providing high adhesive strength. Each of the compounds of Formula 1, compounds of Formula 2, oligomers, and polymers below has a polyoxyalkylene group (e.g., polyoxymethylene), and is therefore expected to interact with the binders and / or fillers described below (e.g., hydrogen bonding) to exhibit an effect of increasing adhesive strength, but this disclosure is not limited thereto.

[0036] It is anticipated that each of the compounds of Formula 1 below, the compounds of Formula 2 below, the oligomers, and the polymers will increase the ionic conductivity of the membrane, thereby providing low membrane resistance, but this disclosure is not limited thereto. In one example, the oligomers and polymers may have a better membrane resistance reduction effect than each of the compounds of Formula 1 and Formula 2.

[0037] Compounds of chemical formula 1 are represented by the following chemical formula 1: Chemical Formula 1: .

[0038] In Formula 1, R1 to R6 are each independently a hydrogen atom or a substituted or unsubstituted C1 to C10 alkyl group.

[0039] For example, in Formula 1, all of R1 to R6 may be independently C1 to C10 alkyl groups. For example, in Formula 1, all of R1 to R6 may be independently hydrogen atoms. For example, in Formula 1, at least one of R1 to R6 may be or include a C1 to C10 alkyl group, and at least one of R1 to R6 may be a hydrogen atom. For example, in Formula 1, at least one of R1 to R6 may be hydrogen.

[0040] Compounds of Formula 1 may include 1,3,5-trioxane (TRX, trioxymethylene or 1,3,5-trioxane) represented by Formula 1-1 below: Chemical formula 1-1: .

[0041] Compounds of Formula 1 may include at least one of the following: compounds represented by Formulas 1-2 below, compounds represented by Formulas 1-3 below, compounds represented by Formulas 1-4 below, or any combination thereof: Chemical formulas 1-2: .

[0042] Chemical formulas 1-3: .

[0043] Chemical formulas 1-4: .

[0044] In one example, both the oligomer and the polymer can be formed via a ring-opening reaction of a compound of Formula 1. The ring-opening reaction can be carried out by heating the compound of Formula 1. Heating can be provided by drying and / or aging during the coating manufacturing process, heat generation within the battery, etc. In one example, both the oligomer and the polymer can include polyoxymethylene as repeating units. The formation of polyoxymethylene oligomers and polyoxymethylene polymers via the ring-opening reaction of TRX is well known.

[0045] Here, oligomers can refer to substances with a lower weight-average molecular weight compared to polymers.

[0046] Compounds of chemical formula 2 are represented by the following chemical formula 2: Chemical formula 2: .

[0047] In chemical formula 2, R7 to R14 Each is independently a hydrogen atom or a substituted or unsubstituted C1 to C10 alkyl group.

[0048] For example, in chemical formula 2, R7 to R 14 All of them may be or include C1 to C10 alkyl groups independently. For example, in formula 2, R7 to R... 14 All of them can be hydrogen atoms independently. For example, in chemical formula 2, R7 to R... 14 At least one of them may be or include a C1 to C10 alkyl group, and R7 to R 14 At least one of them can be a hydrogen atom.

[0049] Compounds of Formula 2 may include 1,4-dioxane (1,4-dioxane or dioxane) represented by Formula 2-1 below: Chemical formula 2-1: .

[0050] Compounds of chemical formula 2 may include at least one of the following: compounds represented by chemical formula 2-2 below, compounds represented by chemical formula 2-3 below, compounds represented by chemical formula 2-4 below, or any combination thereof: Chemical formula 2-2: .

[0051] Chemical formula 2-3: .

[0052] Chemical formula 2-4: .

[0053] In one example, both the oligomer and the polymer can be formed via a ring-opening reaction of a compound of Formula 2. The ring-opening reaction can be carried out by heating the compound of Formula 2. Heating can be provided by drying and / or aging during the coating manufacturing process, heat generation within the battery, etc. In one example, both the oligomer and the polymer can include polyoxymethylene groups as repeating units.

[0054] One or more of the compounds of Formula 1, Formula 2, oligomers, and polymers may be included in the coating in an amount ranging from about 0.01 wt% to about 10 wt% (e.g., 0.1 wt% to 5 wt%). Within the above range, the effect of providing high adhesive strength and low membrane resistance of the diaphragm can be enhanced.

[0055] For example, the coating may include one or more of a compound of Formula 1, an oligomer of a compound of Formula 1, and a polymer of a compound of Formula 1.

[0056] Additives can be included at any location within the coating. In one example, additives can be included at the interface between the coating and the porous substrate, on the outermost surface of the coating, and / or within the coating. For example, additives can be included within the coating to increase the degree of interaction between the binder and / or filler, thereby enhancing the effect of improving the adhesive strength of the diaphragm.

[0057] The adhesive may include one or more of heat-resistant adhesives and adhesive adhesives.

[0058] Heat-resistant adhesive: Heat-resistant binders can further increase the high-temperature life of batteries by further reducing the thermal shrinkage rate of the separator.

[0059] Heat-resistant adhesives may be or include water-based (meth)acrylic adhesives.

[0060] Heat-resistant binders may have functional groups that interact with additives. These functional groups may be one or more of hydroxyl, amide, carboxylic acid, cyano, sulfonic acid, sulfonate, and sulfonate groups. For example, the functional group may be an amide group. The amide group can have a high degree of hydrogen bonding with the additive, thereby increasing the membrane's effectiveness.

[0061] Heat-resistant adhesives may include structural units derived from (meth)acrylates or (meth)acrylic acid, structural units containing cyano groups, structural units derived from (meth)acrylamide, and structural units containing sulfonic acid groups, sulfonate groups, or sulfonate groups, or one or more of these.

[0062] In one example, the heat-resistant adhesive may have structural units derived from (meth)acrylamide and structural units containing sulfonic acid groups, sulfonate groups, or sulfonate groups. In another example, the heat-resistant adhesive may have structural units derived from (meth)acrylamide, structural units containing sulfonate groups, and structural units derived from (meth)acrylates or (meth)acrylic acid.

[0063] The sulfonate-containing structural units may be included in the (meth)acrylic adhesive in an amount of about 0.1 mol% to about 60 mol% (e.g., 0.1 mol% to 20 mol%, 0.1 mol% to 10 mol%, 1 mol% to 20 mol%, e.g., 1 mol% to 10 mol%, e.g., 20 mol% to 65 mol%, 30 mol% to 65 mol%). When the content of the sulfonate-containing structural units is within the above range, the membrane may exhibit desired or improved adhesive strength, heat resistance, air permeability, and oxidation resistance.

[0064] Structural units derived from (meth)acrylate or (meth)acrylic acid may be included in the (meth)acrylic acid binder in an amount ranging from about 0 mol% to about 70 mol% (e.g., 10 mol% to 70 mol%, 10 mol% to 60 mol%, 20 mol% to 60 mol%, 10 mol% to 50 mol%, 30 mol% to 60 mol%, 10 mol% to 40 mol%, or 40 mol% to 55 mol%). Within the above range, the diaphragm may exhibit desired or improved adhesive strength, heat resistance, air permeability, and oxidation resistance.

[0065] The cyano-containing structural units may be included in the (meth)acrylic adhesive in an amount from about 0 mol% to about 85 mol% (e.g., 30 mol% to 85 mol%, 30 mol% to 70 mol%, 30 mol% to 60 mol%, 35 mol% to 60 mol%, or 35 mol% to 55 mol%). Within the above range, the diaphragm can ensure desired or improved oxidation resistance and exhibit adhesive strength, heat resistance, and air permeability.

[0066] Structural units derived from (meth)acrylamide may be included in the (meth)acrylic acid binder in an amount ranging from about 0 mol% to about 95 mol% (e.g., 40 mol% to 85 mol%, 50 mol% to 85 mol%, 55 mol% to 95 mol%, 60 mol% to 85 mol%, 75 mol% to 95 mol%, or 80 mol% to 95 mol%). Within the above range, the membrane can ensure desired or improved oxidation resistance and exhibit adhesive strength, heat resistance, and air permeability.

[0067] According to one example embodiment, the (meth)acrylic adhesive may have, for example, about 0.1 mol% to about 30 mol% (e.g., 0.1 mol% to 10 mol%) of sulfonate-containing structural units, for example, about 10 mol% to about 60 mol% (e.g., 10 mol% to 40 mol%) of structural units derived from (meth)acrylate or (meth)acrylic acid, and for example, about 30 mol% to about 85 mol% (e.g., 30 mol% to 80 mol%) of cyano-containing structural units. In one example, based on 100 mol% of the (meth)acrylic adhesive, the sum of the sulfonate-containing structural units, the structural units derived from (meth)acrylate or (meth)acrylic acid, and the cyano-containing structural units may be about 95 mol% or more, for example, in the range of about 95 mol% to about 100 mol% or 100 mol%.

[0068] According to another example embodiment, the (meth)acrylic adhesive may have, for example, structural units containing sulfonate groups in the range of about 1 mol% to about 20 mol% (e.g., 5 mol% to 20 mol%) and structural units derived from (meth)acrylamide in the range of about 80 mol% to about 99 mol% (e.g., 80 mol% to 95 mol%). In one example, based on 100 mol% of the (meth)acrylic adhesive, the sum of the structural units containing sulfonate groups and the structural units derived from (meth)acrylamide may be about 95 mol% or more, for example, in the range of about 95 mol% to about 100 mol% or 100 mol%.

[0069] According to another example embodiment, the (meth)acrylic adhesive may have structural units containing sulfonate groups, structural units derived from (meth)acrylate or (meth)acrylic acid, and structural units derived from (meth)acrylamide. In one example, based on 100 mol% of the (meth)acrylic adhesive, the sum of the structural units containing sulfonate groups, the structural units derived from (meth)acrylate or (meth)acrylic acid, and the structural units derived from (meth)acrylamide may be about 95 mol% or more, for example, in the range of about 95 mol% to about 100 mol% or 100 mol%.

[0070] The structural units of the (meth)acrylic adhesive are described in detail.

[0071] Structural units derived from (meth)acrylates or (meth)acrylic acid can be represented by at least one of the following chemical formulas 3, 4, 5, or combinations thereof: Chemical formula 3: .

[0072] Chemical formula 4: .

[0073] Chemical formula 5: .

[0074] In chemical formulas 3 to 5, R 1 To R 6 Each is independently hydrogen or methyl, and in Formula 4, M is or includes an alkali metal. An alkali metal may be or includes at least one of, for example, lithium, sodium, potassium, rubidium, or cesium.

[0075] For example, structural units derived from (meth)acrylates or (meth)acrylic acid may include structural units represented by Formula 4 and structural units represented by Formula 5, in which case the structural units represented by Formula 4 and structural units represented by Formula 5 may be included in a molar ratio in the range of about 10:1 to about 1:2 or 10:1 to 1:1 or 5:1 to 1:1.

[0076] Structural units containing cyano groups can be represented, for example, by the following chemical formula 6: Chemical Formula 6: .

[0077] In chemical formula 6: R 7 and R 8 Each is independently hydrogen or C1 to C3 alkyl. L 1 It is or includes -C(=O)-, -C(=O)O-, -OC(=O)-, -O-, or -C(=O)NH-. x is an integer in the range of 0 to 2. L 2 It is or includes substituted or unsubstituted C1 to C10 alkylene groups, substituted or unsubstituted C3 to C20 cycloalkylene groups, substituted or unsubstituted C6 to C20 arylene groups, or substituted or unsubstituted C3 to C20 heterocyclic groups, and y is an integer in the range of 0 to 2.

[0078] The cyano-containing structural unit may be derived, for example, from (meth)acrylonitrile, olefin nitrile, (meth)acrylic acid cyanoalkyl ester, or 2-(ethoxy)alkane nitrile. Here, olefin may be or include C2 to C20 olefins, C2 to C10 olefins, or C2 to C6 olefins; alkyl may be or include C1 to C20 alkyl, C1 to C10 alkyl, or C1 to C6 alkyl; and alkane may be or include C1 to C20 alkanes, C1 to C10 alkanes, or C1 to C6 alkanes.

[0079] Olefin nitrile can be or includes, for example, allyl cyanide, 4-pentenonitrile, 3-pentenonitrile, 2-pentenonitrile, or 5-hexenonitrile. (Meth)acrylate cyanoalkyl ester can be (meth)acrylate methyl cyanoacrylate, (meth)acrylate ethyl cyanoacrylate, (meth)acrylate propyl cyanoacrylate, or (meth)acrylate octyl cyanoacrylate. 2-(ethoxy)alkane nitrile can be or includes, for example, 2-(ethoxy)acetonitrile or 2-(ethoxy)propionitrile.

[0080] The structural unit containing a sulfonate group can be or includes a structural unit containing a conjugate base of sulfonic acid, sulfonate, sulfonate, or a derivative thereof. For example, the structural unit containing a sulfonate group can be represented by at least one of the following chemical formulas 7, 8, 9, or combinations thereof.

[0081] Chemical Formula 7: .

[0082] Chemical formula 8: .

[0083] Chemical formula 9: .

[0084] In chemical formulas 7 to 9: R 9 To R 14 Each is independently hydrogen or C1 to C3 alkyl. L 3 L 5 and L 7 Each is independently -C(=O)-, -C(=O)O-, -OC(=O)-, -O-, or -C(=O)NH-. L 4 L 6 and L 8 Each is independently or comprises a substituted or unsubstituted C1 to C10 alkylene group, a substituted or unsubstituted C3 to C20 cycloalkylene group, a substituted or unsubstituted C6 to C20 arylene group, or a substituted or unsubstituted C3 to C20 heterocyclic group, and a, b, c, d, e, and f are each an independent integer in the range of 0 to 2, and In chemical formula 8, M is or includes alkali metals.

[0085] For example, in chemical formulas 7 to 9: L 3 L 5 and L 7 Each is independently either -C(=O)NH- or includes -C(=O)NH-. L 4 L 6 and L 8 Each is independently or comprises C1 to C10 alkylene groups. Furthermore, a, b, c, d, e, and f can be integers equal to 1.

[0086] The structural unit containing a sulfonate group can be derived, for example, from vinylsulfonic acid, allylsulfonic acid, styrenesulfonic acid, anethole sulfonic acid, (meth)acrylamidoalkyl sulfonic acid, (meth)acrylate sulfonyl ester, or a salt thereof. Here, the alkane can be or includes C1 to C20 alkanes, C1 to C10 alkanes, or C1 to C6 alkanes, and the alkyl group can be or includes C1 to C20 alkyl groups, C1 to C10 alkyl groups, or C1 to C6 alkyl groups. The salt consists of or includes the aforementioned sulfonic acid and suitable ions. The ions can be or include, for example, alkali metal ions; in this case, the salt can be or includes an alkali metal sulfonate salt.

[0087] (Methacrylamidoalkanesulfonic acid) can be at least one of 2-(meth)acrylamido-2-methylpropanesulfonic acid, and (meth)acrylic acid sulfonyl ester can be (meth)acrylic acid 2-sulfoethyl ester, (meth)acrylic acid 3-sulfopropyl ester, etc.

[0088] The structural unit derived from (meth)acrylamide can be represented by chemical formula 10.

[0089] Chemical Formula 10: .

[0090] In chemical formula 10: R 15 and R 16 Each can be either hydrogen or methyl.

[0091] (Meth)acrylic binders may include alkali metals. Alkali metals may be present in cationic form and may be, for example, lithium, sodium, potassium, rubidium, or cesium. For example, alkali metals may be combined with (meth)acrylic binders and present in the form of salts. Alkali metals can facilitate the synthesis of (meth)acrylic binders in aqueous solvents, enhance the adhesive strength of coatings, and improve the heat resistance, permeability, and oxidation resistance of the membrane.

[0092] Alkali metals may be included between the alkali metal and the (meth)acrylic binder in an amount of about 1 wt% to about 40 wt%, for example, in an amount of 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 10 wt% to 20 wt%. For example, the (meth)acrylic binder and the alkali metal may be included in a weight ratio ranging from about 99:1 to about 60:40 or a weight ratio of 99:1 to 70:30 (e.g., a weight ratio of 99:1 to 80:20, for example, a weight ratio of 90:10 to 80:20).

[0093] Furthermore, based on the total content of alkali metal and (meth)acrylic binder, the alkali metal content can range from about 0.1 mol% to about 1.0 mol%. When the alkali metal content is within the above range, the coating can have the desired or improved adhesive strength, and the diaphragm including the coating can exhibit the desired or improved heat resistance, air permeability, and oxidation resistance.

[0094] (Meth)acrylic adhesives can take various forms, such as alternating copolymers with alternating structural units, random polymers with randomly distributed structural units, or grafted polymers in which some structural units are grafted.

[0095] The weight-average molecular weight (Mw) of the (meth)acrylic adhesive can range from 200,000 g / mol to 700,000 g / mol (e.g., 200,000 g / mol to 600,000 g / mol or 300,000 g / mol to 600,000 g / mol). Within this range, the membrane can exhibit desired or improved adhesive strength, heat resistance, air permeability, and oxidation resistance. The weight-average molecular weight here can be the average molecular weight converted from polystyrene as measured using gel permeation chromatography.

[0096] The glass transition temperature of the aforementioned (meth)acrylic adhesive can be in the range of about 200°C to about 280°C (e.g., 210°C to 270°C or 210°C to 260°C). Within this range, the diaphragm can exhibit desired or improved adhesive strength, heat resistance, air permeability, and oxidation resistance. The glass transition temperature can be measured, for example, by differential scanning calorimetry.

[0097] (Meth)acrylic adhesives can have a melting point (Tm) of about 160°C or higher.

[0098] (Meth)acrylic acid binders can be prepared by solution polymerization.

[0099] According to one example embodiment, the (meth)acrylic adhesive may be included in the coating of the diaphragm in the form of a film.

[0100] Adhesive adhesives: Adhesive binders can increase the adhesive strength of the separator, thereby increasing the battery's room temperature life and high temperature life.

[0101] The adhesive can be a water-based adhesive.

[0102] Adhesive binders may have functional groups that interact with additives. These functional groups may be one or more of hydroxyl, amide, carboxylic acid, cyano, sulfonic acid, sulfonate, and sulfonate groups. For example, the functional groups may be one or more of hydroxyl and carboxylic acid groups. Hydroxyl and carboxylic acid groups can have high hydrogen bonding with the additives, thereby increasing the effect of improving the adhesive strength of the membrane.

[0103] In one example, the adhesive may include one or more of polyvinyl alcohol, polyacrylic acid, and polyvinyl alcohol-polyacrylic acid copolymers. One or more of polyvinyl alcohol, polyacrylic acid, and polyvinyl alcohol-polyacrylic acid copolymers, by having the aforementioned functional groups, can significantly increase the effect of improving the adhesive strength of the diaphragm.

[0104] In one example, the adhesive binder may include poly(methyl methacrylate). Poly(methyl methacrylate) does not interact with additives but can increase the adhesive strength of the membrane. For example, poly(methyl methacrylate) may be or include particulate aqueous binders.

[0105] In one example, the adhesive may include one or more of polyvinyl alcohol, polyacrylic acid, and polyvinyl alcohol-polyacrylic acid copolymer, as well as poly(methyl methacrylate).

[0106] In one example, the adhesive binder may comprise about 80 wt% to about 99 wt% (e.g., 90 wt% to 99 wt%) of poly(methyl methacrylate) and about 1 wt% to about 20 wt% (e.g., 1 wt% to 10 wt%) of one or more of polyvinyl alcohol, polyacrylic acid, and polyvinyl alcohol-polyacrylic acid copolymers. Within the above range, the adhesive strength of the diaphragm can be further increased, and when combined with additives, the effect of the diaphragm can be further enhanced.

[0107] filler: The coating may also include fillers.

[0108] The filler can have a particle size (or particle size) D50 of about 0.7 μm or smaller. Within this range, the diaphragm can easily provide a low rate of thermal shrinkage. For example, the filler can have a particle size D50 in the range of about 0.1 μm to about 0.7 μm.

[0109] The filler may be or includes, for example, inorganic fillers, organic fillers, organic-inorganic composite fillers, or combinations thereof. Inorganic fillers may be or include ceramic materials capable of improving heat resistance. Inorganic fillers may include, for example, at least one of metal oxides, quasi-metal oxides, metal fluorides, metal hydroxides, or combinations thereof. Inorganic fillers may include, but are not limited to, at least one of Al₂O₃, SiO₂, TiO₂, SnO₂, CeO₂, MgO, NiO, CaO, GaO, ZnO, ZrO₂, Y₂O₃, SrTiO₃, BaTiO₃, Mg(OH)₂, boehmite, or combinations thereof. Organic fillers may include, but are not limited to, at least one of acrylic compounds, imide compounds, amide compounds, or combinations thereof. Organic fillers may have a core-shell structure, but are not limited to this.

[0110] The packing material can be spherical, plate-shaped, cubic, or without a fixed shape. For example, the packing material can be cubic.

[0111] In one example, the filler may have functional groups that interact with the additive (e.g., form hydrogen bonds with the additive). The functional groups may be or include one or more of hydroxyl, amide, carboxylic acid, cyano, sulfonic acid, sulfonate, and sulfonate groups. For example, the functional group may be or include hydroxyl groups. Hydroxyl groups can have high hydrogen bonding with the additive, thereby increasing the membrane's effectiveness. For example, the filler may be boehmite. Boehmite can have high interaction with the additive by having hydroxyl groups on its surface.

[0112] The mixture of heat-resistant binder and additives, along with fillers, can be included in a mass ratio ranging from about 1:10 to about 1:50 (e.g., 1:15 to 1:30). Within this range, the adhesive strength of the diaphragm can be increased.

[0113] The structure of the coating: The coating may include additives, heat-resistant adhesives, adhesive binders and / or fillers, and the coating may have a structure of one or more layers.

[0114] In one example, the coating may be a single layer, and the single layer may include a heat-resistant adhesive, filler, and additives.

[0115] Figure 1 This is a cross-sectional view showing a diaphragm according to an example embodiment. (Refer to...) Figure 1 The diaphragm may include a porous substrate 1 and a coating 2 formed on the porous substrate 1, and the coating 2 may include filler 3, heat-resistant binder 4, and additives (in... Figure 1 (Not shown in the image).

[0116] In one example, the coating may include filler in the range of about 80 wt% to about 99 wt% (e.g., 90 wt% to 99 wt%) and heat-resistant binder and additives in the range of about 1 wt% to about 20 wt% (e.g., 1 wt% to 10 wt%). Within the above range, the effect of a diaphragm can be readily achieved.

[0117] The heat-resistant binder can be included in the coating in an amount ranging from about 0.5 wt% to about 10 wt% (e.g., 0.5 wt% to 5 wt%), and the additive can be included in the coating in an amount ranging from about 0.2 wt% to about 10 wt% (e.g., 0.2 wt% to 5 wt% or 0.2 wt% to 3 wt%). Within the above ranges, the diaphragm effect can be readily achieved.

[0118] In another example, the coating may be a two-layer coating comprising a first layer and a second layer, the first layer comprising a heat-resistant adhesive, filler and additives, and the second layer formed on the first layer and comprising an adhesive adhesive.

[0119] The second layer may also include additives.

[0120] Figure 2 This is a cross-sectional view showing a diaphragm according to an example embodiment. (Refer to...) Figure 2 The diaphragm may include a porous substrate 1 and a coating 2 formed on the porous substrate 1, and the coating 2 may include: a first layer 5, comprising a filler 3, a heat-resistant binder 4, and additives (in... Figure 2 (not shown); and the second layer 7, including adhesive 6 and additives (in Figure 2 (Not shown in the image).

[0121] In one example, the first layer may comprise filler in the range of about 80 wt% to about 99 wt% (e.g., 90 wt% to 99 wt%) and heat-resistant binder and additives in the range of about 1 wt% to about 20 wt% (e.g., 1 wt% to 10 wt%). Within the above range, the diaphragm effect can be readily achieved.

[0122] The heat-resistant binder can be included in the first layer in an amount ranging from about 0.5 wt% to about 10 wt% (e.g., 0.5 wt% to 5 wt%), and the additive can be included in the first layer in an amount ranging from about 0.2 wt% to about 10 wt% (e.g., 0.2 wt% to 5 wt%). Within the above ranges, the effect of the diaphragm can be easily achieved.

[0123] In one example, the second layer may be or include about 100 wt% adhesive.

[0124] In another example, the second layer may comprise about 90 wt% to 99.8 wt% (e.g., 95 wt% to 99.8 wt% or 97 wt% to 99.8 wt%) of an adhesive binder and about 0.2 wt% to 10 wt% (e.g., 0.2 wt% to 5 wt% or 0.2 wt% to 3 wt%) of additives. Within the above range, the diaphragm effect can be readily achieved.

[0125] In one example, the second layer may comprise about 90 wt% to 98 wt% (e.g., 90 wt% to 95 wt%) of poly(methyl methacrylate), about 0.1 wt% to 8 wt% (e.g., 0.5 wt% to 5 wt%) of polyvinyl alcohol, polyacrylic acid, and polyvinyl alcohol-polyacrylic acid copolymer, and about 0.2 wt% to 10 wt% (e.g., 0.5 wt% to 5 wt%) of additives. Within the above range, the diaphragm effect can be readily achieved.

[0126] In another example, the coating may include a third layer, which includes a heat-resistant adhesive, an adhesive binder, fillers, and additives.

[0127] Figure 3 This is a cross-sectional view showing a diaphragm according to an example embodiment. (Refer to...) Figure 3 The diaphragm may include a porous substrate 1 and a coating 2 formed on the porous substrate 1, and the coating 2 may include a filler 3, a heat-resistant adhesive 4, an adhesive 6, and additives (in... Figure 3 (Not shown in the image).

[0128] In one example, the coating may include fillers ranging from about 80 wt% to about 99 wt% (e.g., 90 wt% to 99 wt%) and heat-resistant binders, adhesive binders, and additives totaling from about 1 wt% to about 20 wt% (e.g., 1 wt% to 10 wt%). Within the above range, the diaphragm effect can be readily achieved.

[0129] The coating may have a thickness in the range of about 0.01 μm to about 20 μm, and within the above range, it may have a thickness in the range of about 1 μm to about 10 μm, or 1 μm to 5 μm, or 1 μm to 3 μm.

[0130] A coating can be formed by applying a composition for coating onto a porous substrate to a predetermined or desired thickness, and then curing the composition at a temperature in the range of about 85°C to about 120°C for about 15 hours or longer (e.g., a duration in the range of about 15 hours to about 24 hours).

[0131] Porous substrate: Porous substrates can be or include substrates with a plurality of pores commonly used in electrochemical devices. Porous substrates can be, or include, polymer membranes, which are formed or comprise any one of the following polymers or copolymers or mixtures thereof, or include any one of the following polymers or copolymers or mixtures thereof, such as or including at least one of polyolefins (e.g., polyethylene and polypropylene), polyesters (e.g., polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetheretherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (e.g., Teflon).

[0132] The porous substrate can be, for example, a polyolefin substrate comprising polyolefins, and the polyolefin substrate can have the desired or improved shutdown function, thus contributing to improved battery safety. The polyolefin substrate can be or include at least one of, for example, polyethylene monolayer film, polypropylene monolayer film, polyethylene / polypropylene bilayer film, polypropylene / polyethylene / polypropylene trilayer film, and polyethylene / polypropylene / polyethylene trilayer film. For example, in addition to olefin resins, the porous substrate can also include non-olefin resins, or can include copolymers of olefin monomers and non-olefin monomers.

[0133] The porous substrate can have a thickness in the range of about 1 μm to about 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm or 5 μm to 15 μm.

[0134] According to an example embodiment, the diaphragm can exhibit desired or improved air permeability. For example, the diaphragm can have an air permeability value of less than about 200 seconds / 100cc (e.g., less than or equal to 190 seconds / 100cc or less than or equal to 180 seconds / 100cc). In other words, the diaphragm can have an air permeability value per unit thickness of less than 40 seconds / 100cc·1μm (e.g., less than or equal to 30 seconds / 100cc·1μm or less than or equal to 25 seconds / 100cc·1μm). Here, air permeability refers to the time (in seconds) it takes for 100cc of air to pass through a unit thickness of the diaphragm. The air permeability per unit thickness can be obtained by measuring the air permeability of the entire thickness of the diaphragm and then dividing that air permeability by the thickness. The air permeability can be measured using an air permeability measuring device (Asahi Seiko, EG01-55-1MR) to measure the time (in seconds) it takes for 100cc of air to pass through.

[0135] Rechargeable lithium batteries According to one example embodiment, a rechargeable lithium battery includes a separator, a positive electrode, and a negative electrode for the rechargeable lithium battery.

[0136] The separator used in rechargeable lithium batteries is described above. The separator for rechargeable lithium batteries can be located between the positive and negative electrodes.

[0137] positive electrode The positive electrode for a rechargeable lithium battery may include a current collector and a layer of positive electrode active material on the current collector. The positive electrode active material layer may include positive electrode active material and may also include a binder and / or conductive material. For example, the positive electrode may also include additives that can constitute a sacrificial positive electrode.

[0138] Positive electrode active material The positive electrode active material may include compounds capable of intercalating and deintercalating lithium (lithiation intercalation compounds). For example, at least one of the composite oxides of lithium and metals such as or including at least one of cobalt, manganese, nickel, and combinations thereof may be used.

[0139] The composite oxide can be or includes lithium transition metal composite oxides. Examples of composite oxides may include at least one of lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, cobalt-free lithium nickel manganese oxides, or combinations thereof.

[0140] As an example, the following compounds, represented by any of the following chemical formulas, can be used. Li a A 1-b X b O 2- c D c (0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5 and 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5 and 0<α<2); Li a Nib Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0≤e≤0.1); Li a NiG b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 1-b G b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8 and 0≤g≤0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); or Li a FePO4 (0.90≤a≤1.8).

[0141] In the above chemical formula, A is or includes at least one of Ni, Co, Mn, or combinations thereof; X is or includes at least one of Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, or combinations thereof; D is or includes at least one of O, F, S, P, or combinations thereof; G is or includes at least one of Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or combinations thereof; and L 1 It is or includes at least one of Mn, Al, or combinations thereof.

[0142] The positive electrode active material can be, or includes, for example, a high-nickel positive electrode active material, based on 100 mol% of metal other than lithium in a lithium transition metal complex oxide. The nickel content of the high-nickel positive electrode active material is greater than or equal to about 80 mol%, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. High-nickel positive electrode active materials can achieve high capacity and can be applied to high-capacity, high-density rechargeable lithium batteries.

[0143] Based on a 100 wt% positive electrode active material layer, the amount of positive electrode active material can range from about 90 wt% to about 99.5 wt%. Based on a 100 wt% positive electrode active material layer, the amounts of binder and conductive material can each independently range from about 0.5 wt% to about 5 wt%.

[0144] The binder causes the positive electrode active material particles to adhere to each other and to adhere the positive electrode active material to the current collector. As a non-limiting example, examples of binders may include at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, nylon, etc.

[0145] Conductive materials can impart electrical conductivity (e.g., electroconductivity) to electrodes. Any material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in rechargeable lithium batteries) and conducts electrons can be used in the battery. Examples of conductive materials may include: carbon-based materials, such as at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials, including at least one of copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.

[0146] Al can be used as a current collector, but current collectors are not limited to this.

[0147] negative electrode The negative electrode for a rechargeable lithium battery may include a current collector and a layer of negative electrode active material on the current collector. The negative electrode active material layer may include a negative electrode active material and may also include a binder and / or a conductive material (e.g., an electrically conductive material).

[0148] For example, the negative electrode active material layer may include a negative electrode active material in the range of about 90 wt% to about 99 wt%, a binder in the range of about 0.5 wt% to about 5 wt%, and a conductive material in the range of about 0 wt% to about 5 wt%.

[0149] Negative electrode active material The negative electrode active material may include at least one of the following: materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials capable of doping / dedoping lithium, or transition metal oxides.

[0150] The material capable of reversibly intercalating / deintercalating lithium ions may include a carbon-based negative electrode active material, such as crystalline carbon, amorphous carbon, or a combination thereof as examples. The crystalline carbon may be or include graphite, such as natural graphite or artificial graphite in an amorphous, flaky, lamellar, spherical, or fibrous form. The amorphous carbon may be or include at least one of soft carbon, hard carbon, mesophase pitch carbonized products, calcined coke, and the like.

[0151] Lithium metal alloys include alloys of lithium with at least one metal such as or including Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0152] The material capable of doping / dedoping lithium may be or include a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0<x≤2), or at least one of Si-Q alloys (wherein Q is or includes at least one of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof). The Sn-based negative electrode active material may include at least one of Sn, SnO₂, a Sn-based alloy, or a combination thereof.

[0153] The silicon-carbon composite may be or include a composite of silicon and amorphous carbon. According to exemplary embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) assembled from primary silicon particles, and an amorphous carbon coating (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0154] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating on the surface of the core.

[0155] The Si-based negative electrode active material or the Sn-based negative electrode active material may be used in combination with the carbon-based negative electrode active material.

[0156] The binder may cause the negative electrode active material particles to adhere to each other, and may cause the negative electrode active material to adhere to the current collector. The binder may include a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.

[0157] Non-aqueous adhesives may include at least one of polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.

[0158] The waterborne adhesive may be or include at least one of styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0159] When using an aqueous binder as the negative electrode binder, it may also include a cellulose compound capable of imparting viscosity. The cellulose compound may include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or an alkali metal salt thereof. The alkali metal may include at least one of Na, K, or Li.

[0160] Dry adhesives can be or include polymeric materials capable of being fibrous. For example, dry adhesives can be or include at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0161] Conductive materials can impart electrical conductivity (e.g., electroconductivity) to electrodes. Any material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in a rechargeable lithium battery) and conducts electrons can be used in the battery. Non-limiting examples of conductive materials may include: carbon-based materials, such as at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metallic materials, including at least one of copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fibers; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.

[0162] The negative electrode current collector may include at least one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.

[0163] Rechargeable lithium batteries may also include an electrolyte solution.

[0164] Electrolyte solution Electrolyte solutions used in rechargeable lithium batteries may include non-aqueous organic solvents and lithium salts.

[0165] Non-aqueous organic solvents can serve as media for transporting ions that participate in the electrochemical reactions of a battery.

[0166] Non-aqueous organic solvents may be or include at least one of carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or combinations thereof.

[0167] Carbonate solvents may include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC).

[0168] Ester solvents may include at least one of the following: methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.

[0169] Ether solvents may include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc. Aprotic solvents may include at least one of the following: nitriles, such as R-CN (wherein R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether bonds, etc.); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane; etc.

[0170] Non-aqueous organic solvents can be used alone or in combination of two or more solvents.

[0171] Furthermore, when using carbonate solvents, cyclic carbonates and chain carbonates can be mixed together, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio ranging from about 1:1 to about 1:9.

[0172] Lithium salts dissolved in organic solvents supply lithium ions in batteries, enabling rechargeable lithium batteries to operate essentially and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, and LiN(C x F 2x+1 SO2)(C y F2y+1 At least one of the following: (SO2) (where x and y are integers in the range of 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluoro(oxalate)borate (LiDBOB), lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0173] Rechargeable lithium batteries can be classified according to their shape as cylindrical batteries, prismatic batteries, pouch batteries, or coin-shaped batteries, etc.

[0174] Figures 4 to 7 This is a schematic diagram illustrating a rechargeable lithium battery according to an example embodiment. Figure 4 A cylindrical battery is shown. Figure 5 A prismatic battery is shown, and Figure 6 and Figure 7 A pouch-type battery is shown. (See reference) Figures 4 to 7 The rechargeable lithium battery 100 may include an electrode assembly 40 and a housing 50. The electrode assembly 40 includes a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). Figure 4 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of a sealed housing 50. Figure 5 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12 connected to the positive electrode lead connector 11, a negative electrode lead connector 21, and a negative electrode terminal 22 connected to the negative electrode lead connector 21. For example... Figure 6 and Figure 7 As shown, the rechargeable lithium battery 100 may include Figure 7 The electrode terminal 70 shown, or for example Figure 6 The positive electrode terminal 71 and negative electrode terminal 72 shown herein form an electrical path for guiding the current generated in the electrode assembly 40 to the outside of the rechargeable lithium battery 100.

[0175] As a non-limiting example, the rechargeable lithium battery according to the example embodiment can be used in, for example, automobiles, mobile phones and / or various types of electrical devices.

[0176] Examples and comparative examples of this disclosure are described below. However, the following examples are merely examples of this disclosure, and this disclosure is not limited to these examples.

[0177] Preparation Example Add distilled water (6,361 g), acrylamide (9.5 mol), potassium persulfate (0.01 mol), 2-acrylamide-2-methylpropanesulfonic acid (0.5 mol), and 5N lithium hydroxide aqueous solution (based on a total amount of 1.05 equivalents of 2-acrylamide-2-methylpropanesulfonic acid) to a 10 L four-necked flask equipped with a stirrer, thermometer, and condenser. Reduce the internal pressure to 10 mmHg using a diaphragm pump, and restore the internal pressure to atmospheric pressure using nitrogen. Repeat this operation 3 times.

[0178] The reaction proceeded for 12 hours, while the temperature of the reaction solution was maintained stable between 65°C and 70°C. After cooling to room temperature, the pH of the reaction solution was adjusted to between 7 and 8 using a 25% ammonia solution.

[0179] Lithium poly(acrylamide-co-2-acrylamide-2-methylpropanesulfonic acid) was prepared in this manner. The molar ratio of acrylamide to 2-acrylamide-2-methylpropanesulfonic acid was 95:5. Approximately 10 mL of the reaction solution (reaction product) was taken, and the amount of non-volatile components was determined to be 9.5 wt% (theoretical value 10 wt%).

[0180] Example 1 The acrylic binder (10 wt% in distilled water) prepared in the preparation example was mixed with boehmite (particle size D50: 200 nm, plate-shaped) as filler, and the resulting mixture was placed in water as solvent, milled at 25°C for 30 minutes using a bead mill, and dispersed to prepare a dispersion.

[0181] TRX was added to the dispersion, and water was added to bring the total solids content to 20 wt%, thereby preparing a composition for the first layer. The composition for the first layer comprises 95 wt% boehmite, 4.5 wt% acrylic binder, and 0.5 wt% TRX.

[0182] A composition for the second layer was prepared by mixing 95 parts by weight of poly(methyl methacrylate) (PMMA, a particulate waterborne binder), 4.5 parts by weight of polyvinyl alcohol-polyacrylic acid copolymer (PVA-PAA), and 0.5 parts by weight of TRX.

[0183] The composition for the first layer was coated onto both surfaces of a polyethylene film (thickness: 8 μm, SK, air permeability: 120 s / 100 cc, puncture strength: 480 kgf) serving as a porous substrate to a thickness of 2 μm using a molding process. The film was then dried and cured in an oven at 85°C for 16 hours to produce the first layer. The composition for the second layer was coated onto one surface of the first layer to a thickness of 0.5 μm, and then dried and cured in an oven at 85°C for 16 hours to produce the diaphragm.

[0184] Examples 2 and 3, and comparison example 1 The membrane is manufactured in the same manner as in Example 1, except that the components of the first and second layers in Example 1 are changed as shown in Table 1 below.

[0185] Battery manufacturing Lithium cobalt oxide (LCO, LiCoO) as the positive electrode active material, polyvinylidene fluoride as the binder, and carbon nanotubes (CNTs) as the conductive material were mixed in a weight ratio of 98.7:0.9:0.4, and the resulting mixture was dispersed in N-methylpyrrolidone to prepare a positive electrode slurry. The prepared positive electrode slurry was coated onto one surface of a 10 μm thick aluminum current collector using a reverse roller coater to a concentration of 19.8 mg / cm². 2 The loading level (L / L) is then adjusted and dried at 110°C. The resulting positive electrode active material layer is calendered using a roll press to fabricate the positive electrode.

[0186] Artificial graphite (as the negative electrode active material), styrene-butadiene rubber (SBR) (as a binder), and carboxymethyl cellulose (CMC) (as a thickener) were mixed in a weight ratio of 97.5:1.5:1, and the resulting mixture was added to an aqueous solvent to prepare a negative electrode slurry. The prepared negative electrode slurry was coated onto both surfaces of a 10 μm thick copper foil using a reverse roll coater and then dried at 120 °C. The resulting negative electrode active material layer was calendered using a roll press to manufacture the negative electrode.

[0187] The diaphragm manufactured in the above examples and comparative examples was placed between the positive and negative electrodes manufactured above, and then wound to manufacture the electrode assembly core. The core was inserted into a bag, electrolyte was injected, and the bag was vacuum sealed. The electrolyte used was 1.3 M LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC), and propylene propionate (PP) in a volume ratio of 10:15:75 (based on a total volume of 100). The core inserted into the bag was pressed at 80°C for three minutes while applying 11.7 kgf / cm². 2 The pressure is to manufacture rechargeable lithium batteries.

[0188] Wet bond strength (unit: N / 25mm) Each separator in the example and comparative examples was cut to a size of 25 mm wide and 80 mm long. The positive electrode, manufactured as described above, was cut to a size of 30 mm wide and 80 mm long. The positive electrode was placed on one surface of each separator and on the other surface to manufacture the cell.

[0189] The electrolyte (1.3 M LiPF6 dissolved in a mixed solvent of EC, PC, and PP at a volume ratio of 10:15:75 based on a total volume of 100) was injected into a 10 cm × 10 cm bag, and the cell was inserted into the bag. The cells were immersed for 12 hours and then subjected to immersion at 80 °C and 300 kgf / cm². 2 The bonding was carried out under the specified conditions for 1 hour. After removing the diaphragm and positive electrode from the bag, the positive electrode and diaphragm were unfolded 180°, and the force required to tear the positive electrode from the diaphragm was measured using a tensile testing machine (Tinius Olsen, HT400).

[0190] The wet bond strength of the negative electrode was measured using the negative electrode manufactured as described above, in the same manner as the wet bond strength of the positive electrode.

[0191] Membrane resistance (unit: Ω) The membrane resistance was evaluated as electrochemical impedance spectroscopy (EIS) resistance. Membranes fabricated in the example and comparative examples were impregnated with 1.3 M LiPF6 dissolved in a mixed solvent of EC, PC, and PP in a volume ratio of 10:15:75 (based on a total volume of 100). The resulting membranes were then assembled onto aluminum foil electrodes with leaded terminals and sealed in an aluminum cask to fabricate a test cell. The resistance (Ω) of this test cell was measured at 20°C using AC impedance spectroscopy (measurement frequency 100 kHz).

[0192] Room temperature lifespan (unit: %) A coin cell was fabricated using the negative electrode, positive electrode, separator, and electrolyte prepared above. As the electrolyte, 1.3 M LiPF6 was used dissolved in a mixed solvent of EC, PC, and PP in a volume ratio of 10:15:75 (based on a total volume of 100).

[0193] Using the manufactured rechargeable lithium-ion battery, 200 charge / discharge cycles were performed under the conditions of "25°C, 1.0C charge (CC / CV, 4.5V, 0.02C cutoff) / 1.0C discharge (CC, 3.0V cutoff)," and then the battery characteristics were measured. The lifetime retention rate was calculated according to the equation below.

[0194] Equation: Lifetime retention rate (%) = (Discharge capacity after 200 cycles / Initial discharge capacity) × 100.

[0195] Room temperature life evaluation and thermal shrinkage rate after high temperature storage (unit: %) The room temperature life was evaluated in the same manner as described above. Subsequently, the separator was removed from the battery and cut into 5cm × 5cm pieces to prepare samples. After allowing the samples to stand in an oven at 140°C for one hour, the thermal shrinkage rate was calculated. The thermal shrinkage rate was calculated according to the following equation.

[0196] Equation: Heat shrinkage rate (%) = (L0-L1) / L0×100.

[0197] L0 is the initial area of ​​the diaphragm, and L1 is the area of ​​the diaphragm after standing at 140°C for 1 hour.

[0198] Heat exposure assessment A pouch cell was manufactured using the negative electrode, positive electrode, separator, and electrolyte prepared above. The positive electrode was stamped to a size of 3 × 4 cm, and the negative electrode was stamped to a size of 3.2 × 4.2 cm. The separator was placed between the positive and negative electrodes. 1.3 M LiPF6 was used as the electrolyte, dissolved in a mixed solvent of EC, PC, and PP at a volume ratio of 10:15:75 (based on a total volume of 100). The positive electrode, separator, and negative electrode were then sealed in an aluminum pouch to manufacture the pouch cell. The designed capacity of the manufactured battery was 36 mAh.

[0199] The manufactured rechargeable lithium batteries were exposed to a target temperature (high temperature) for one hour, and then ignition was evaluated. When raising the temperature from room temperature to the target temperature, the heating rate was maintained at 5°C / min. The results were recorded as the number of evaluated batteries and the ratio of non-ignited batteries to ignited batteries.

[0200] Table 1:

[0201] Table 2:

[0202] N = Number of batteries evaluated F = Fire (Failure) OK = Not on fire As shown in Table 2 above, the example separator can provide low thermal shrinkage, long room temperature life, and long high temperature life by offering high wet bond strength. The example separator can provide long room temperature life and long high temperature life by offering low membrane resistance. The example separator can enhance battery safety and reliability by reducing or suppressing ignition of batteries with separators upon thermal exposure.

[0203] A separator for a rechargeable lithium-ion battery according to an example embodiment can provide low thermal shrinkage, long room temperature life, and long high temperature life by providing high adhesive strength (particularly high wet adhesive strength). A separator for a rechargeable lithium-ion battery according to an example embodiment can provide long room temperature life and long high temperature life by providing low film resistance. According to an example embodiment, a separator for a rechargeable lithium-ion battery can improve battery safety and reliability by reducing or suppressing ignition of the battery with the separator upon thermal exposure.

[0204] Although exemplary embodiments of the present disclosure have been described above, the present disclosure is not limited thereto, and various modifications can be made within the scope of the claims, the detailed description of the disclosure, and the drawings, which also fall within the scope of the present disclosure.

Claims

1. A separator for a rechargeable lithium battery, the separator comprising: porous substrate; as well as A coating is applied to at least one surface of the porous substrate. The coating comprises an adhesive and an additive, wherein the additive comprises one or more of a compound of formula 1, a compound of formula 2, oligomers thereof, and polymers thereof: Chemical Formula 1: ; Wherein, R1 to R6 are each independently a hydrogen atom or a substituted or unsubstituted C1 to C10 alkyl group; and Chemical formula 2: ; Among them, R7 to R 14 Each is independently a hydrogen atom or a substituted or unsubstituted C1 to C10 alkyl group.

2. The diaphragm according to claim 1, wherein, In chemical formula 1, at least one of R1 to R6 is hydrogen.

3. The diaphragm according to claim 1, wherein, The compounds of Formula 1 include 1,3,5-trioxane represented by the following Formula 1-1: Chemical formula 1-1: 。 4. The diaphragm according to claim 1, wherein, Both the oligomer and the polymer include polyoxymethylene as repeating units.

5. The diaphragm according to claim 1, wherein, The compound of chemical formula 1, the compound of chemical formula 2, the oligomer, and the polymer are included in the coating in an amount ranging from 0.01 wt% to 10 wt%.

6. The diaphragm according to claim 1, wherein, The adhesive includes one or more of heat-resistant adhesives and adhesive adhesives.

7. The diaphragm according to claim 6, wherein, The heat-resistant adhesive includes one or more of the following groups: hydroxyl, amide, carboxylic acid, cyano, sulfonic acid, sulfonate, and sulfonate ester.

8. The diaphragm according to claim 7, wherein, The heat-resistant adhesive includes: Structural units derived from (meth)acrylamide; and Structural units containing sulfonic acid groups, sulfonate groups, or sulfonate groups.

9. The diaphragm according to claim 6, wherein, The adhesive includes one or more of hydroxyl, amide, carboxylic acid, cyano, sulfonic acid, sulfonate, and sulfonate groups.

10. The diaphragm according to claim 6, wherein, The coating also includes fillers with a particle size D50 of 0.7 μm or smaller.

11. The diaphragm according to claim 10, wherein, The filler includes functional groups capable of forming hydrogen bonds with the additive.

12. The diaphragm according to claim 10, wherein, The coating comprises the heat-resistant adhesive, the additive, and the filler.

13. The diaphragm according to claim 10, wherein, The coating comprises: The first layer includes the heat-resistant adhesive, the additive, and the filler; and The second layer is formed on the first layer and includes the adhesive.

14. The diaphragm according to claim 10, wherein, The coating comprises the heat-resistant adhesive, the adhesive binder, the additive, and the filler.

15. A rechargeable lithium battery, said rechargeable lithium battery comprising: Positive electrode; negative electrode; as well as The separator for a rechargeable lithium battery according to claim 1 is located between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • An Heating pipe water leakage detection method using ultrasonic waves

    KR1020250055071A